Study of clinical and etiological profile of hypertension in young patients - Sheetal Rudra Naik; Mamatha Tittamegalapalya Ramalingaiah; Aishwarya Ram (Asian Journal of Medical Sciences, 2025)
Background: Hypertension significantly impacts global health, leading to coronary heart disease, stroke, and renal disease. Addressing it in young adults is crucial due to its potentially reversible causes and early intervention. Aims and Objectives: (1) To study the clinical profile of newly diagnosed hypertension in young patients (2) To study the etiological profile of hypertension in young. Materials and Methods: In this cross-sectional study after obtaining clearance from the institutional ethics committee, the patients fulfilling the inclusion criteria were enrolled after obtaining informed consent. Data were collected using a pretested proforma, meeting the objectives of the study. A detailed assessment of patients was performed including history and clinical examination of all systems. Laboratory investigations were conducted and analyzed. Results: The mean age of participants was 34.38±4.729 years, with 63% being male. Common symptoms included headache (18%) and giddiness (18%). A significant proportion (58%) had secondary hypertension, primarily due to renal and endocrine causes. Essential hypertension accounted for 42% of cases. The mean systolic and diastolic blood pressures were 178.06±14.112 mmHg and 92.17±11.441 mmHg, respectively. Lifestyle factors such as smoking and alcohol use were noted in 12% and 4% of participants, respectively. Conclusion: Early detection and management of hypertension in young adults are crucial to prevent long-term complications. Secondary hypertension is common in this demographic, requiring specific treatments.